2011
DOI: 10.1128/jvi.01524-10
|View full text |Cite
|
Sign up to set email alerts
|

Novel F141L Pre-S2 Mutation in Hepatitis B Virus Increases the Risk of Hepatocellular Carcinoma in Patients with Chronic Genotype C Infections

Abstract: Several lines of evidence have suggested that some naturally occurring mutations of hepatitis B virus (HBV) play a critical role in hepatocellular carcinoma (HCC). Here, we describe a novel HCC-related pre-S2 mutation, F141L. To prove the relationship between the F141L mutation and HCC, molecular epidemiology studies using MboII PCR restriction analysis (PRA) were performed, and the molecular mechanism was investigated through construction of a stable hepatocyte cell line expressing the large surface HB protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 26 publications
0
50
0
Order By: Relevance
“…However, the other RCT [38] in our review found that NA therapy significantly decreased early HCC recurrence, while it did not report outcomes on late HCC recurrence. NA therapy may inhibit early HCC recurrence, which usually arises due to diffusion of the primary tumor, by reducing high HBV load and HBV mutations, all of which are associated with HCC metastasis and growth [40][41][42] , as well as by inhibiting HBxAg, which promotes HCC invasiveness and metastatic potential [43,44] . Further studies are urgently needed to clarify whether and how NA therapy affects risk of HCC recurrence, since the results of RCT [38] in our review may overestimate the NA efficacy because the control group at baseline had significantly higher rates of cirrhosis, lower rates of tumor encapsulation, and higher rates of HBeAg positivity than the NA group, as well as poorer tumor differentiation and higher AFP levels.…”
Section: Recurrence-free Survivalmentioning
confidence: 99%
“…However, the other RCT [38] in our review found that NA therapy significantly decreased early HCC recurrence, while it did not report outcomes on late HCC recurrence. NA therapy may inhibit early HCC recurrence, which usually arises due to diffusion of the primary tumor, by reducing high HBV load and HBV mutations, all of which are associated with HCC metastasis and growth [40][41][42] , as well as by inhibiting HBxAg, which promotes HCC invasiveness and metastatic potential [43,44] . Further studies are urgently needed to clarify whether and how NA therapy affects risk of HCC recurrence, since the results of RCT [38] in our review may overestimate the NA efficacy because the control group at baseline had significantly higher rates of cirrhosis, lower rates of tumor encapsulation, and higher rates of HBeAg positivity than the NA group, as well as poorer tumor differentiation and higher AFP levels.…”
Section: Recurrence-free Survivalmentioning
confidence: 99%
“…The HBV large envelope protein gene fragment (preS1/ preS2/S), with F141L mutation in the preS2 region, can significantly promote the proliferation of hepatocytes by downregulating the p53 and p21 pathways and upregulating the expression of cyclin-dependent kinase 4 and cyclin A. The colony-forming rates of hepatocytes expressing F141L-large envelope protein are about twice as high as those expressing the wild-type HBV large envelope protein [58] . Random integration of HBV DNA into the host genome is present in HBVinfected subjects.…”
Section: Reduction Of Cd8mentioning
confidence: 93%
“…Furthermore, the result of bimolecular assays suggested that substitutions and deletion of nucleotides of HBV genome, including G1317A, T1341 C/A/G and pre-S2 deletion may lead to elevated risk of developing hepatocelluar carcinoma, on the other hand, those mutations may capable of serving as the predictor of liver cancer among patients with genotype C chronic hepatitis (Zhang et al, 2007). The latest approach by using Mboll PCR restriction analysis also identified a novel mutation in pre-S2, it is reported that F141L mutation was significantly related to HCC, even in comparison to live cirrhosis among 241 Korean patients (Mun et al, 2011). As for pre-S deletion, it was (Gao et al, 2007) reported that these mutations were more commonly found in the patients with HCC that in the chronic hepatitis B or asymptomatic carrier, suggesting pre-S deletion might involved in HBV-related hepatocarinogenesis.…”
Section: Hbv Infectionmentioning
confidence: 99%